Betawi Ethnic Parents' Perceptions of Girls' Higher Education - Made Saihu (Randwick International of Education and Linguistics Science Journal, 2022)
This paper concludes that parents of Betawi ethnicity in Tangerang city area have different perceptions about higher education for their daughters. Some of the differences in perception include: 1) Considering higher education very important, because women when they are married and have children, the mother becomes the "first madrasa" for her children and the intelligent mother will give birth to an intelligent generation as well; 2) Consider it unimportant, because they assume that girls when married are more focused at home to be housewives; 3) Although many of the Betawi ethnic parents expect higher education in their children, many of them are at a weak economic level. In principle, this paper aims to photograph the phenomenon of reasoning of Betawi ethnic parents related to higher education for girls in Tangerang City. In its analysis, this paper uses a descriptive qualitative method that assumes that researchers are not only actors in the field but can also be the subject of research. This research is indeed considered less than perfect; therefore, it is necessary to conduct further research at least through this research to provide an overview of how Betawi ethnic perspectives concern higher education for their girls. A study that describes social phenomena in the perspective of ethnomethodology in Betawi society.